Cardiovascular Effects of Walking Tumamoc Hill and Relavence with Individuals with Down Syndrome - Seacat, Michael Joseph (The University of Arizona., 2013)
This project involved studying the historic site of Tumamoc Hill in West Tucson and its associated conservation efforts, research, and public use. We looked at the anatomy and physiology of the cardiovascular system, and the components and functions of the heart, blood vessels, and blood. We studied Down Syndrome and common heart defects associated with the trisomy of chromosome 21. We then looked at the acute and chronic cardiovascular adaptations associated with exercise, and additional exercise-related considerations needed for individuals with Down Syndrome. After studying these topics, Dr. Zoe Cohen, Alyson Fix, and Michael Seacat hiked Tumamoc Hill and distributed brochures incorporating learned information to hikers that were "Rocking the Moc." Experiences and findings were presented at the Physiology Poster Session on April 17, 2013.